Explant Sterilization of Sandalwood (Santalum album) and Teak (Tectona grandis) Micropropagation with Commercial Disinfectant - Sulaiman, Helmi; Ramadhani, Shabrina Yasmin; Wicaksana, Kresna Fajri; Kartiwijaya, Rosadi; Rahmawati, Dewi; Suryani, Dewi; Ardiansyah, Rhomi (BIODIVERS - BIOTROP Science Magazine, 2023)
Sandalwood (Santalum album) and Teak (Tectona grandis) are essential wood sources for furniture. Sustainable micropropagation methods can benefit wood availability. This study evaluates NaOCl and Povidone-iodine effects, immersion duration, and concentrations on teak and sandalwood micropropagation. Teak is treated with 10% & 15% NaOCl and 10% & 15% Povidone-iodine. No significant difference was observed between teak treatments; however, povidone-iodine shows potential as an effective teak sterilizing agent. Sandalwood's best sterilization: NaOCl at 10% & 15%.